Description of a third species in the alpheid shrimp genus Richalpheus Anker & Jeng, 2006 (Crustacea, Decapoda) - Anker, Arthur (Zootaxa, 2011)
A new species of the alpheid genus Richalpheus Anker & Jeng, 2006 is described from the Egyptian Red Sea and Moorea, French Polynesia. Richalpheus alpheoides sp. nov. differs from the two previously described species of this genus, R. palmeri Anker & Jeng, 2006 and R. dahabensis Dworschak & Anker, 2007, by the presence of a distinct proximal tooth on the dactylus fitting into a shallow fossa on the pollex of the major chela, reminiscent of the snapping mechanism in Alpheus Fabricius, 1798. Recently collected material of R. palmeri from Moorea is reported, whilst a specimen previously reported as R. palmeri is reassigned to R. alpheoides sp. nov. A key to the three known species of Richalpheus is provided.